Letter to the Editor: Exercise Interventions and Cardiovascular Health in Childhood Cancer: A Meta-Analysis - da Costa Ghignatti, Paola Victória; Pereira de Lima, Ricardo (International Journal of Sports Medicine, 2020)
Dear Editor,International Journal of Sports MedicineThe analysis of the study entitled “Exercise Interventions and Cardiovascular Health in Childhood Cancer: a Meta-Analysis” 1 was very interesting. The authors of this meta-analysis aimed to summarize the evidence on the effects of physical training intervention over three weeks on cardiovascular and cardiorespiratory outcomes in childhood cancer survivors (CCS). In addition, they addressed endpoints related not only to cardiac structure and function, but also to cardiorespiratory fitness.